2017
DOI: 10.1073/pnas.1714386114
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human IRAK1

Abstract: Interleukin 1 (IL-1) receptor-associated kinases (IRAKs) are serine/threonine kinases that play critical roles in initiating innate immune responses against foreign pathogens and other types of dangers through their role in Toll-like receptor (TLR) and interleukin 1 receptor (IL-1R) mediated signaling pathways. Upon ligand binding, TLRs and IL-1Rs recruit adaptor proteins, such as myeloid differentiation primary response gene 88 (MyD88), to the membrane, which in turn recruit IRAKs via the death domains in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 41 publications
7
75
0
Order By: Relevance
“…It has not proved possible to over-express full-length IRAK1 and TRAF6 in E. coli, although various sub-domains of these proteins have been successfully produced (Fu et al 2018;Ye et al 2002;Wang et al 2017). This is most likely because both enzymes are multi-domain human proteins, most of which are notoriously recalcitrant to expression in recombinant bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not proved possible to over-express full-length IRAK1 and TRAF6 in E. coli, although various sub-domains of these proteins have been successfully produced (Fu et al 2018;Ye et al 2002;Wang et al 2017). This is most likely because both enzymes are multi-domain human proteins, most of which are notoriously recalcitrant to expression in recombinant bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Toll-like receptor 7 (TLR7) and TLR9 are among various pattern recognition receptors that sense viral nucleic acids and induce production of type I interferons by plasmacytoid dendritic cells (pDCs) to protect the host from viral infection (Wu and Chen 2014). As a component of this pathway, viperin stimulates the K63-linked polyubiquitination of interleukin-1 receptor-associated kinase (IRAK1) (Wang et al 2017;Conze et al 2008;Honda et al 2004) by the E3 ubiquitin ligase, TRAF6 (Saitoh et al 2011;Conze et al 2008). K63-linked poly-ubiquitination, in turn, activates IRAK1 to phosphorylate interferon regulatory factor 7 (IRF7), causing IRF7 to migrate to the nucleus where it activates transcription of type 1 interferons (Honda et al 2004;Honda et al 2006) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…41 IRAK1 belongs to a family of serine/threonine kinases and plays a vital role in the immune response by serving as a key molecule in the Toll-like receptor signaling pathway. 42 TRAF6 is identified as an actor downstream of multiple receptor families, including the Toll-like receptor signaling pathway, and can promote the activation of the transcription factor NF-ÎșB. 43 Based on current research, SMAD4, TRAF6, and IRAK1 are all predominantly enriched in the inflammatory signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The MyD88-dependent pathway is activated by the TLR4 ligand LPS. Upon ligand binding, TLRs recruit adaptor proteins MyD88, activating the IRAK1 and IRAK4, enabling the recruitment of TNF receptor-associated factor 6 (TRAF6), which phosphorylates transforming growth factor-b-activated kinase 1 binding protein 2/3 (TAB2/TAB3) and transforming growth factor-b-activated kinase 1 (TAK1), leading to the activation of the NF-kB and MAPK signaling pathway (Ajibade et al, 2013;Wang et al, 2017). Our data showed that GH downregulated the activation of TLR4-MyD88 signaling pathway in RAW 264.7 cells and BMDMs.…”
Section: Discussionmentioning
confidence: 99%